Analysis between ABO blood group and clinical outcomes in COVID-19 patients and the potential mediating role of ACE2 - Zeng, Xianfei; Fan, Hongyan; Kou, Jinxin; Lu, Dongxue; Huang, Fang; Meng, Xi; Liu, Haiying; Li, Zhuo; Tang, Mei; Zhang, Jing; Liu, Nannan; Hu, Xingbin (Frontiers in Medicine, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become the most common coronavirus that causes large-scale infections worldwide. Currently, several studies have shown that the ABO blood group is associated with coronavirus disease 2019 (COVID-19) infection and some studies have also suggested that the infection of COVID-19 may be closely related to the interaction between angiotensin-converting enzyme 2 (ACE2) and blood group antigens. However, the relationship between blood type to clinical outcome in critically ill patients and the mechanism of action is still unclear. The current study aimed to examine the correlation between blood type distribution and SARS-CoV-2 infection, progression, and prognosis in patients with COVID-19 and the potential mediating role of ACE2. With 234 patients from 5 medical centers and two established cohorts, 137 for the mild cohort and 97 for the critically ill cohort, we found that the blood type A population was more sensitive to SARS-CoV-2, while the blood type distribution was not relevant to acute respiratory distress syndrome (ARDS), acute kidney injury (AKI), and mortality in COVID-19 patients. Further study showed that the serum ACE2 protein level of healthy people with type A was significantly higher than that of other blood groups, and type O was the lowest. The experimental results of spike protein binding to red blood cells also showed that the binding rate of people with type A was the highest, and that of people with type O was the lowest. Our finding indicated that blood type A may be the biological marker for susceptibility to SARS-CoV-2 infection and may be associated with potential mediating of ACE2, but irrelevant to the clinical outcomes including ARDS, AKI, and death. These findings can provide new ideas for clinical diagnosis, treatment, and prevention of COVID-19.